1999
DOI: 10.1007/s002130050997
|View full text |Cite
|
Sign up to set email alerts
|

Acute behavioral effects and abuse potential of trazodone, zolpidem and triazolam in humans

Abstract: The present study examined the acute behavioral effects and abuse potential of three drugs commonly used to treat sleep disorders, trazodone, zolpidem and triazolam, and placebo in ten male volunteers with histories of alcohol and drug abuse. Trazodone (100, 200 and 300 mg), a triazolopyridine antidepressant, was included because antidepressants are being used more frequently to treat sleep disorders, but it is unclear whether they have a distinct behavioral pharmacologic profile relative to benzodiazepine hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 24 publications
2
48
1
2
Order By: Relevance
“…The absence of motor and cognitive impairment after ramelteon ingestion in the present study contrasts with findings from previous studies demonstrating impairing effects after administration of a range of hypnotic drugs, including benzodiazepine receptor agonists (eg, zolpidem, 44 lorazepam, 46 triazolam, 35 oxazepam, 47 and zaleplon 12 ) and other compounds (eg, pentobarbital sodium, 35 diphenhydramine hydrochloride, 54 and trazodone hydrochloride 55 ). Previous results of sleep efficacy investigations of ramelteon are consistent with the present study in finding no motor or cognitive-impairing effects.…”
Section: Commentcontrasting
confidence: 56%
“…The absence of motor and cognitive impairment after ramelteon ingestion in the present study contrasts with findings from previous studies demonstrating impairing effects after administration of a range of hypnotic drugs, including benzodiazepine receptor agonists (eg, zolpidem, 44 lorazepam, 46 triazolam, 35 oxazepam, 47 and zaleplon 12 ) and other compounds (eg, pentobarbital sodium, 35 diphenhydramine hydrochloride, 54 and trazodone hydrochloride 55 ). Previous results of sleep efficacy investigations of ramelteon are consistent with the present study in finding no motor or cognitive-impairing effects.…”
Section: Commentcontrasting
confidence: 56%
“…Early investigations seemed to indicate little evidence of abuse or dependence (Darcourt et al 1999). However, several recent studies have demonstrated that these medications do have significant abuse potential (Ravishankar and Carnwath 1998;Rush et al 1999), particularly at high doses and in patients with a history of substance dependence (Hajak et al 2003;Soyka et al 2000). Withdrawal seizures have also been seen at supra-therapeutic doses (Aragona 2000).…”
Section: Drug Definitionmentioning
confidence: 98%
“…There is some indication that zolpidem can have an anxiolytic effect at higher doses and that with increasing dose of zolpidem for sleep can lead to withdrawal side effects during the daytime. 4 The guideline also states that the duration of treatment should usually vary from a few days to two weeks with a maximu m of four weeks, including tapering off where appropriate. 5 However, recently concern has been raised regarding the dependence potential of these Z-drugs.…”
Section: Introductionmentioning
confidence: 99%